(untitled) (Geologica Macedonica, 2016)
The purpose of the investigations presented in the paper is the determination of the level of underground water for a geologically researched area. On the basis of the geological data are determined the vertical faults and contacts that can be assessed as accumulating areas with possible presence of exploitable amount of underground water.The geophysical approach is based on the preliminary geological investigations as well as the measurable physical parameters, and ultimately is reduced to the application of methods that records electromagnetic waves with very low frequency (VLF) and geoelectrical investigations performed with the method of vertical electrical sounding. The geophysical surveys are applied in stages where the VLF method initially is used as a prospective investigation obtained through three profile lines (positioned transverse of the assumed fault zones), whereas the electrical resistance research is used as an investigative method to define the depth to the assumed water bearing structure. The VLF surveys are obtained through evaluation of the electromagnetic field and filtering the obtained data through different determined depths and are performed with the instrument WADI. The electrical investigations are performed with the instrument TERRASAS 1000.